2017
DOI: 10.1007/8904_2017_26
|View full text |Cite
|
Sign up to set email alerts
|

Glutaric Acidemia Type 1: A Case of Infantile Stroke

Abstract: Background: Glutaric acidemia Type 1 (GA-1) is an autosomal recessively inherited metabolic disorder which is associated with GCDH gene mutations which alters the glutaryl-CoA dehydrogenase, an enzyme playing role in the catabolic pathways of the amino acids lysine, hydroxylysine, and tryptophan. Clinical findings are often encephalopathic crises, dystonia, and extrapyramidal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The majority of inborn errors of metabolism cause brain injury. Metabolic stroke and SLEs are manifestations of these injuries (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(36)(37)(38)(39)(40)(41)(42). The most common inborn errors of metabolism that potentially predispose patients to metabolic stroke are outlined in Table 2.…”
Section: Other Inherited Metabolic Diseases and Strokementioning
confidence: 99%
“…The majority of inborn errors of metabolism cause brain injury. Metabolic stroke and SLEs are manifestations of these injuries (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(36)(37)(38)(39)(40)(41)(42). The most common inborn errors of metabolism that potentially predispose patients to metabolic stroke are outlined in Table 2.…”
Section: Other Inherited Metabolic Diseases and Strokementioning
confidence: 99%
“…Glutaric acidemia type 1 affects around the world, about 1 in every 100,000 children, macrocephaly is an important feature, is present in about 75% of cases and may already be present at birth, which shows intrauterine expression. Clinical manifestations appear until the second year of life and present in an acute or chronic form [3,6,7]. www.jcimcr.org Page 2 Table 2 shows the measurement of the head circumference of the cases presented.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The disease affects about 1 per 100,000 individuals, has an autosomal recessive inheritance and the GCDH gene, located in 19p13.2, is related to this acidemia [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…5 Kaya Ozcora et al reported infantile stroke in a 9-month-old child with GA1. 27 Badve et al reported a 32-year-old female patient with GA1, who presented with migraine and a bipolar disorder with frontal lobe dysfunction and bilateral pyramidal tract signs. 28 Young-Lin et al reported a 7-month-old male infant with GA1, who presented with flexor spasms, video electroencephalography revealed hypsarrhythmia and the child improved with prednisolone.…”
Section: Rare Complicationsmentioning
confidence: 99%